Can a teaching assistant experience in a surgical anatomy course influence the learning curve for nontechnical skill development for surgical residents?. Issue 1 (30th June 2015) - Heidenreich, Mark J.; Musonza, Tashinga; Pawlina, Wojciech; Lachman, Nirusha
Abstract : The foundation upon which surgical residents are trained to work comprises more than just critical cognitive, clinical, and technical skill. In an environment where the synchronous application of expertise is vital to patient outcomes, the expectation for optimal functioning within a multidisciplinary team is extremely high. Studies have shown that for most residents, one of the most difficult milestones in the path to achieving professional expertise in a surgical career is overcoming the learning curve. This view point commentary provides a reflection from the two senior medical students who have participated in the Student‐as‐Teacher program developed by the Department of Anatomy at Mayo Clinic, designed to prepare students for their teaching assistant (TA) role in anatomy courses. Both students participated as TAs in a six week surgical anatomy course for surgical first assistant students offered by the School of Health Sciences at Mayo Clinic. Development of teaching skills, nontechnical leadership, communication, and assessment skills, are discussed in relation to their benefits in preparing senior medical students for surgical residency. Anat Sci Educ. © 2015 American Association of Anatomists.